2014
DOI: 10.1371/journal.pone.0086263
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tissue microRNAs Predictive of Sunitinib Activity in Patients with Metastatic Renal Cell Carcinoma

Abstract: PurposeTo identify tissue microRNAs predictive of sunitinib activity in patients with metastatic renal-cell-carcinoma (MRCC) and to evaluate in vitro their mechanism of action in sunitinib resistance.MethodsWe screened 673 microRNAs using TaqMan Low-density-Arrays (TLDAs) in tumors from MRCC patients with extreme phenotypes of marked efficacy and resistance to sunitinib, selected from an identification cohort (n = 41). The most relevant differentially expressed microRNAs were selected using bioinformatics-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 34 publications
6
74
0
2
Order By: Relevance
“…These findings are consistent with the observation that primary and metastatic tumours remain epigenetically similar 237 . Several studies have analysed the presence of multiple mi RNAs in serum from patients with RCC to provide prognostic information and identify renal-specific cancers [240][241][242] . The use of miRNA profiles to predict treatment response has also been proposed and two studies have identified panels of mi RNAs that are associated with different responses to sunitinib, an FDA-approved treatment for RCC 243,244 .…”
Section: Prognosismentioning
confidence: 99%
“…These findings are consistent with the observation that primary and metastatic tumours remain epigenetically similar 237 . Several studies have analysed the presence of multiple mi RNAs in serum from patients with RCC to provide prognostic information and identify renal-specific cancers [240][241][242] . The use of miRNA profiles to predict treatment response has also been proposed and two studies have identified panels of mi RNAs that are associated with different responses to sunitinib, an FDA-approved treatment for RCC 243,244 .…”
Section: Prognosismentioning
confidence: 99%
“…Also, Berkers et al [58] showed that miRNA was related to the response to sunitinib as tested in 20 mRCC patients: a significantly lower expression of miRNA-141 was observed for poor responders [58]. On miRNA expression of miRNA, Prior et al [59] identified miRNA-942, miR-628-5p, miR133a, and miR-484 as predictors for sunitinib efficacy (i.e. time to progression, OS, and resistance).…”
Section: Micro Rna In Sunitinib Treatmentmentioning
confidence: 99%
“…time to progression, OS, and resistance). It was postulated that high levels of miRNA-942 will stimulate the secretion of matrix metalloproteinase-9 and VEGF and thereby effectuate resistance to sunitinib [59].…”
Section: Micro Rna In Sunitinib Treatmentmentioning
confidence: 99%
“…Egyik tanulmány szerint a miR-141 a sunitinib kezelésre nehezen reagáló eseteknél jelentősen downreguláltnak mutatkozott (9,30). Egy másik elemzés alapján a miR-942 volt a legpontosabb előrejelzője a sunitinib érzékenységnek (31). Magas miR-942, -628-5p, -133a és -484 expressziója jelentősen ösz-szefügg a metasztatikus Rcc-esetek előrehaladásával, valamint a túléléssel is, amit az is igazol, hogy ezek a miR-ek a sunitinib rezisztens cAKI-2 humán Rcc-sejtvonalban is abnormális mértékben expresszálódtak az érzékeny sejtvonalhoz képest (9,31).…”
Section: A Mir-ek Lehetséges Prognosztikai Szerepeunclassified
“…Egy másik elemzés alapján a miR-942 volt a legpontosabb előrejelzője a sunitinib érzékenységnek (31). Magas miR-942, -628-5p, -133a és -484 expressziója jelentősen ösz-szefügg a metasztatikus Rcc-esetek előrehaladásával, valamint a túléléssel is, amit az is igazol, hogy ezek a miR-ek a sunitinib rezisztens cAKI-2 humán Rcc-sejtvonalban is abnormális mértékben expresszálódtak az érzékeny sejtvonalhoz képest (9,31). A közelmúltban lett igazolva a miR-199a-3p sejtproliferációt gátló és a sejtciklus G1 fázisát blokkoló tulajdonsága a cAKI-1 Rcc-sejtvonalban (32).…”
Section: A Mir-ek Lehetséges Prognosztikai Szerepeunclassified